1999
DOI: 10.1038/eye.1999.47
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of endothelin-1 in diabetic retinopathy in pregnancy

Abstract: This study has shown that ET-1 levels rise during normal pregnancy, and are higher in women with diabetes, which may reflect pre-existing endothelial damage. Although no association could be demonstrated between diabetic retinopathy and serum ET-1 levels, this may reflect the small sample size in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…They also found that ET-1 serum levels were similar in women with and without vascular complications of diabetes; even in women who experienced preeclampsia ET-1 con- [6,7,19] while ET-1 has even been suggested as a sensitive marker of preeclampsia [8] . Similarly, Best et al [20] reported higher ET-1 serum levels in women with PGDM, and concomitant diabetic retinopathy did not influence these results. Some other reports have confirmed higher ET-1 levels in PGDM women, with peak values achieved at term [21] .…”
Section: Discussionmentioning
confidence: 80%
“…They also found that ET-1 serum levels were similar in women with and without vascular complications of diabetes; even in women who experienced preeclampsia ET-1 con- [6,7,19] while ET-1 has even been suggested as a sensitive marker of preeclampsia [8] . Similarly, Best et al [20] reported higher ET-1 serum levels in women with PGDM, and concomitant diabetic retinopathy did not influence these results. Some other reports have confirmed higher ET-1 levels in PGDM women, with peak values achieved at term [21] .…”
Section: Discussionmentioning
confidence: 80%
“…[ 52 ] Low levels of glycoprotein glycodelin, secreted by the endometrium, which is key in inhibiting E-selectin that promotes leucocyte–endothelium adhesion, has been associated with progression of retinopathy. [ 53 ] Similarly, increased levels of endothelin-1 are speculated to cause endothelial damage in pregnancy leading to pregnancy-induced hypertension and progression of DR.[ 54 ]…”
Section: Hyperglycemia In Pregnancymentioning
confidence: 99%